2016
DOI: 10.4012/dmj.2015-383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcoholic beverages on surface roughness and microhardness of dental composites

Abstract: The aim of this study was to evaluate the microhardness and surface roughness of composite resins immersed in alcoholic beverages. Three composite resins were used: Durafill (Heraeus Kulzer), Z250 (3M-ESPE) and Z350 XT (3M-ESPE). The inital surface roughness and microhardness were measured. The samples were divided into four groups (n=30): G1-artificial saliva; G2-beer; G3-vodka; G4-whisky. The samples were immersed in the beverages 3× a day for 15 min and 30 days. The surface roughness and microhardness assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 29 publications
4
40
0
5
Order By: Relevance
“…One of the results of our study was consistent with a finding of Moraes et al (20) who reported that nano-hybrid resins generally demonstrated inferior properties compared with nano-filled composites, and the behavior of nano-hybrid resin composites was more closely related to that of micro-hybrid than nano-filled materials. Da Silva et al (21) examined the microhardness of nanofilled Filtek Z350 XT, microhybrid Filtek Z250, and microfilled Durafill composites and they found values of 118.40, 123.70, and 39.45 KHN for the composites, respectively. The researchers attributed the lowest values of surface hardness Durafill to it having the highest percentage of organic matrix, based on UDMA, and a lower percentage of inorganic filler.…”
Section: Discussionmentioning
confidence: 99%
“…One of the results of our study was consistent with a finding of Moraes et al (20) who reported that nano-hybrid resins generally demonstrated inferior properties compared with nano-filled composites, and the behavior of nano-hybrid resin composites was more closely related to that of micro-hybrid than nano-filled materials. Da Silva et al (21) examined the microhardness of nanofilled Filtek Z350 XT, microhybrid Filtek Z250, and microfilled Durafill composites and they found values of 118.40, 123.70, and 39.45 KHN for the composites, respectively. The researchers attributed the lowest values of surface hardness Durafill to it having the highest percentage of organic matrix, based on UDMA, and a lower percentage of inorganic filler.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the surface quality of the restorative material influences the clinical performance and durability of restorations 5 , since the maintenance of flat surface decreases early alterations of color and shine, besides of reducing the biofilm growth on surface restoration, which decreases risk of secondary caries lesions and periodontal inflammation [4][5][6][7][8][9] . The roughness present on resin surface can be detected by the tip of the patient's tongue since 0.3µm 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a study (6) on the effects of whisky on composites was evaluated and yielded results parallel to the results of our study. In a study collaborating with our results (22), the effects of alcoholic beverages on surface roughness of different types of composites have compared and beer had found to change the surface roughness the most after following whisky in 1 month. The attributed changes were, likewise in our study, thought to be related with the low pH (4.1) of the related beer.…”
Section: Resultsmentioning
confidence: 99%
“…Water absorbance of the materials could cause plasticisation of organic matrices and accelerate decomposition. Also, ethanol has directly penetrated through the resin matrix, broken down the polymeric structure (25), separated the bonding between the filler and displaced the filler particles finally resulting in inferior mechanical properties of the composites (22), which could be more important than prolonged immersion in water. The alcohol concentrations of regular and dark beer were nearly the same, 6.6 and 6.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%